تأثير مسابقة المسرحية في تنمية مهارة الكلام للطلاب في معهد عائشة للتربية الإسلامية الحديثة بوجونيكورو - Nasywa Nuzila Rahmah Rahmah; Danial Hilmi (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This study focuses on the impact of Arabic drama competitions on improving the speaking skills (maharah kalam) of female students at Pondok Modern Aisyiyah Islamic Boarding School Bojonegoro. Using a qualitative approach, the research explores the experiences and perceptions of the students through in-depth interviews and direct observations. The findings indicate that drama competitions not only serve as a platform for contest but also play a significant role in enhancing various aspects of the students’ Arabic language proficiency. Notably, the competitions boost the students’ confidence to speak in public, enrich their vocabulary, improve pronunciation, and enhance their overall speaking fluency. Furthermore, the study reveals that drama competitions strengthen the bonds of sisterhood among students, foster teamwork, create a communicative and interactive learning environment, and encourage the use of Arabic in real-life daily situations within the boarding school. In conclusion, Arabic drama competitions have proven to be an effective learning strategy for improving students' speaking skills and motivating them to communicate actively in Arabic in a modern Islamic boarding school setting, going beyond mere theoretical knowledge towards practical language use.